1993
DOI: 10.1063/1.354969
|View full text |Cite
|
Sign up to set email alerts
|

Surface and domain structures of ferroelectric crystals studied with scanning force microscopy

Abstract: The understanding of the phenomena of ferroelectricity requires profound knowledge of the ferroelectric domain structure. In this paper we report on the progress of studying ferroelectric domains and domain walls with scanning force microscopy (SFM). Domains and domain walls of ferroelectric crystals of guanidinium aluminum sulfate hexahydrate (GASH) are imaged with SFM. Two sets of complementary results are obtained depending on the operation mode of the instrument. In the non-contact imaging mode (attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 34 publications
1
74
0
Order By: Relevance
“…The recent progress in using SFM as an effective tool for high-resolution visualization of a domain structure in ferroelectric thin films provides the appropriate background for this letter. [3][4][5][6] In a typical retention experiment, a capacitor is written into a polarization state and left in that state for fixed periods of time, after which the polarization remaining in the capacitor is measured, as illustrated, for example, in Fig. 1͑a͒.…”
Section: ͓S0003-6951͑97͒00550-0͔mentioning
confidence: 99%
“…The recent progress in using SFM as an effective tool for high-resolution visualization of a domain structure in ferroelectric thin films provides the appropriate background for this letter. [3][4][5][6] In a typical retention experiment, a capacitor is written into a polarization state and left in that state for fixed periods of time, after which the polarization remaining in the capacitor is measured, as illustrated, for example, in Fig. 1͑a͒.…”
Section: ͓S0003-6951͑97͒00550-0͔mentioning
confidence: 99%
“…Recently, it has been demonstrated that scanning force microscopy ͑SFM͒ is a useful technique for investigation of ferroelectric materials, providing high-resolution visualization of ferroelectric domains. [2][3][4][5][6] In the present letter we use SFM to perform a study of domain structures and switching behavior of PZT ferroelectric thin films integrated into heterostructures with different electrodes, which yield different fatigue characteristics.…”
Section: H Tokumotomentioning
confidence: 99%
“…One possible approach is to utilize scanning probe microscopy (SPM) technology because it can easily access nano scaled devices. Thus, recently, SPM has been widely employed for various applications either by the measurement of electrical properties [1] or by the monitoring of the physical properties [2,3]. In particular, in ferroelectric related fields, various techniques based on SPM technology have been developed for the to analysis of ferroelectric films as well as devices.…”
Section: Introductionmentioning
confidence: 99%